The art of changing course a 3-step strategy to get unstuck and solve your real problems - Ruden, Chris (Ascent Audio, 2024)
Getting stuck in life is a guarantee. Staying stuck is a choice. In The Art of Changing Course, amputee, diabetic record-holding powerlifter, and renowned motivational speaker and author Chris Ruden provides a clear-cut process that walks listeners through digestible, actionable stages to get unstuck, allowing you to rise beyond simple awareness of the desire to change and become the person you truly want to be. Backed by numerous psychological principles, management techniques, and organizational change theories, The Art of Changing Course focuses on helping listeners make three distinct shifts: from subconscious to conscious, conscious to communicated, and finally, communicated to broadcasted. In this book, you'll learn about: moving past your go-to reactions of excuses and distractions when thinking about change; harnessing the language of how you speak to yourself to open up possibilities for change; and giving yourself intrinsic permission to become the best version of yourself. People are stuck, lost, and confused-you, the people you care about, and strangers you interact with in your day-to-day life. The Art of Changing Course will give you the tools to actually do something about it. It will help you move from overwhelm to action, transforming from hopeless, scared, and stuck into confident, actionable, and limitless.
Online resource; title from title details screen (O'Reilly, viewed September 24, 2024)
Keywords: Self-actualization (Psychology) -- Popular works; Audiobooks; Livres audio